1997
DOI: 10.1007/pl00005022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gastroprokinetic agents on gastroparesis in streptozotocin-induced diabetic rats

Abstract: The influence of diabetic hyperglycemia on solid gastric emptying in rats was examined. Diabetes was produced by streptozotocin (STZ, 40 mg/kg i.v.), and diabetic hyperglycemia was observed from 1 day after the STZ injection. The gastric emptying of glass beads in the diabetic rats was significantly delayed compared with that in age-matched control rats at 1, 3 and 7 days after diabetes induction. A slight decrease in gastric emptying was observed in the diabetic rats from 2 to 52 weeks after the diabetes indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
2
26
2
1
Order By: Relevance
“…Delayed gastric emptying was consistently reported within 2 weeks after STZ injection [26], whereas the findings were controversial 4 weeks or more after STZ injection [27, 28]. A recent study by Miyamoto et al [27] reported an accelerated gastric emptying at 4 weeks after STZ injection, whereas in this study, we observed a significant delay in gastric emptying 6 weeks after STZ injection.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Delayed gastric emptying was consistently reported within 2 weeks after STZ injection [26], whereas the findings were controversial 4 weeks or more after STZ injection [27, 28]. A recent study by Miyamoto et al [27] reported an accelerated gastric emptying at 4 weeks after STZ injection, whereas in this study, we observed a significant delay in gastric emptying 6 weeks after STZ injection.…”
Section: Discussioncontrasting
confidence: 56%
“…While gastric slow waves have never been studied previously in STZ-diabetic rats, gastric emptying was documented in a number of previous studies [26,27,28] with conflicting results. Delayed gastric emptying was consistently reported within 2 weeks after STZ injection [26], whereas the findings were controversial 4 weeks or more after STZ injection [27, 28].…”
Section: Discussionmentioning
confidence: 98%
“…However, a 5-HT 2C receptor agonist, WAY 161503, had no effect on gastric emptying or gastrointestinal motility. There are reports that 5-HT 3 receptor agonists reduce gastric emptying and gastrointestinal motility (Yamano et al, 1997;Tominaga et al, 2011). Zhang et al (2008) reported that regulative effects of the essential oil of Atractylodes lancea on delayed gastric emptying were performed through the inhibition of the release of central CRF and activation of vagal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although the gastric emptying of beads is not completely comparable to the emptying of digestible solid food as the beads have to be pushed in toto through the pylorus, the method is used as a measure of solid gastric emptying (Yamano et al 1997). The gastric emptying of the beads did not significantly differ between the 3 investigated groups, although the values ranged from 36 to 69%, illustrating the great variability with this method of testing gastric emptying.…”
Section: Discussionmentioning
confidence: 99%